Nursery rearing of Asian catfish (Clarias macrocephalus) in tanks with organic fertilizer and feed inputs - Nacisvalencia, Rosemary Gonzales (University of the Philippines in the Visayas, 1998)
Fifteen-day old clarias macrocephalus fry with an initial body weight of 32.9 + 21.73 mg and total length of 1.41 + 0.31 cm were reared in mud overlaid bottomed concrete tanks either with organic fertilizer (3 mt, /ha and 4.5 mt/ha) and inorganic fertilizer (16-20-0) at a rate of 50 kg/ha or combined organic fertilizer (3 mt/ha), inorganic fertilizer (16-20-0) and supplemental feed for 60 days. Subsequent fertilization with organic fertilizer was applied at 500 kg/ha for Treatment 1 and 3 (applied with 3 mt/ha chicken manure) and 750 kg/ha for Treatment 2 (applied with 4.5 mt/ha chicken manure) every 15 days. Production indices such as mean final body weight (15.67 + 6.69 g),specific growth rate (10.23% + 0.615 per day) and condition factor (0.991 + 0.26) were significantly higher (P<0.05) for C. macrocephalus reared inorganic fertilizer and supplemental feed than for fish reared with organic fertilizer only. Zooplankton density and chlorophyll a concentration were not significantly different among treatments. Ammonia concentration also did not vary significantly among treatments. Carcasses of fingerlings reared with a combination of organic fertilizer and supplemental feed had significantly higher (P<0.05) crude fat (18.58%) and crude protein (16.93%) and a significantly lower ( P<0.05) ash (2.7%) and moisture (74.78%) than those fingerlings reared in tanks with organic fertilizer only. Survival rates (66.65% - 80.90%) did not differ significantly among treatments.